Features of growing epitaxial layers from solid solutions based on indium and aluminium arsenides - Yodgorova, D.M.; Karimov, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Growing the epitaxial layers that contain the aluminium or indium has its specific features. So, the epitaxial layers prepared using the method of liquid-phase epitaxy at high (0.1 to 0.2 at. %) contents of a replacing element can possess a phase non-uniform boundary interface or goffered surface. Height of peaks can run from 2 up to 15 μm in them. The results of researches of diode structures based on epitaxial layers obtained by a combined method are represented in this work. The difference of the used method is that in the beginning growth of a layer goes as that under compulsory cooling, and further as the combined one. So, the melt will be combined due to the solid phase from the epitaxial layer, after admission of the first portion of a solution-melt onto the substrate when cooling the system and another part of the solution-melt will become saturated. In the beginning, the layer grows due to isothermal epitaxy caused by mixing the first and second portions of melts when feeding the next discrete portion of the solution-melt, onto the previous one. After their composition equalization, there takes place a growth caused by compulsory cooling. This way to grow the epitaxial layers can be considered as delta-thermal liquid-phase epitaxy in the multistage process. ΔТ = 3…10 °C is optimum for the initial crystallization temperature Tcr = 750…830 °C.